2008
DOI: 10.1021/ja075367j
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of 2‘-Deoxyguanosine 5‘-Monophosphate Photoinduced by Pterin:  Type I versus Type II Mechanism

Abstract: UV-A radiation (320-400 nm) induces damage to the DNA molecule and its components through different photosensitized reactions. Among these processes, photosensitized oxidations may occur through electron transfer or hydrogen abstraction (type I) and/or the production of singlet molecular oxygen ((1)O2) (type II). Pterins, heterocyclic compounds widespread in biological systems, participate in relevant biological processes and are able to act as photosensitizers. We have investigated the photosensitized oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 54 publications
5
108
1
4
Order By: Relevance
“…More recently, the mechanism involved in the photosensitization of biomolecules by pterins were investigated in a series of studies carried out with free nucleotides [28][29][30] and amino acids [12][13][14]. It was shown that pterins can act as photosensitizers through both type I and type II mechanisms and that the predominant one depends on a combination of many factors, such as quantum yields of Taking into account the studies mentioned in the previous paragraph, a set of competitive mechanisms can be summarized to explain the photooxidation of different biomolecules (S) by pterin derivatives (Pt) (reactions [1][2][3][4][5][6][7][8][9][10][11][12] …”
Section: General Mechanism Of Photooxidation Of Biomolecules By Pterinsmentioning
confidence: 99%
“…More recently, the mechanism involved in the photosensitization of biomolecules by pterins were investigated in a series of studies carried out with free nucleotides [28][29][30] and amino acids [12][13][14]. It was shown that pterins can act as photosensitizers through both type I and type II mechanisms and that the predominant one depends on a combination of many factors, such as quantum yields of Taking into account the studies mentioned in the previous paragraph, a set of competitive mechanisms can be summarized to explain the photooxidation of different biomolecules (S) by pterin derivatives (Pt) (reactions [1][2][3][4][5][6][7][8][9][10][11][12] …”
Section: General Mechanism Of Photooxidation Of Biomolecules By Pterinsmentioning
confidence: 99%
“…In the presence of oxygen, pterin (Ptr) [14], the parent and unsubstituted compound of oxidized pterins, acts as a photosensitizer through both type I (electron transfer or hydrogen abstraction) [15] and type II (production of 1 O 2 ) [16] mechanisms. Moreover, Ptr photoinduces DNA damage and the oxidation of purine nucleotides [17][18][19][20]. Therefore, taking into account the accumulation of pterins in the human skin under pathological conditions described in the previous paragraph, the photochemistry and, especially their photosensitizing properties of these compounds are of particular interest for the study of skin disease.…”
Section: Introductionmentioning
confidence: 99%
“…Under UV-A irradiation, the excited pterins may undergo photooxidation besides fluorescence emission. Pterins, chiefly 6-carboxy pterin, have been shown to photosensitize DNA damage by both type I (electron transfer) and type II (singlet oxygen) mechanisms (19)(20)(21)(22). Despite their important contribution, the electronic and geometrical features of related low-lying states as well as the explicit mechanism of photochemistry and photophysics of pterins are still unclear.…”
Section: Introductionmentioning
confidence: 99%